PENERAPAN INTERNATIONAL SAFETY MANAGEMENT CODE PADA PERUSAHAAN PELAYARAN DI MAKASSAR - Ismail Ismail; Andi Dirga Noegraha; Agriani Pongkessu (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This study aims to obtain an overview of how large the level of implementation of the International Safety Management Code (ISM-Code) is in shipping companies and on ships operating in these companies, and to analyze how they affect the company's operations. The object of this research is a cruise ship company in Makassar, namely PT. Dillah Samudera. This study uses a qualitative descriptive method, where the analysis technique uses two kinds of data, namely primary data which is data obtained through questionnaire interviews and secondary data which is data obtained through literature and documents from companies and related agencies. The results obtained are the level of implementation of the ISM-Code on ships operated by PT. Dillah Samudera obtained an average (mean) according to the scale of 2.21 or 73.67%. As well as implementing the ISM-Code for PT. Ocean Dillah is an average of 2.89 or 96.33%. So it can be determined that the ISM-Code requirements for PT. Most of these Dillah Samudera have complied with the requirements of the ISM-Code. Keywords; Implementation; ISM-Code; Shipping companies